Small Noncoding RNAome Changes During Human Bone Marrow Mesenchymal Stem Cells Senescence In Vitro - Xiao, Fei; Peng, Jianping; Li, Yang; Zhou, Xing; Ma, Ding; Dai, Liming; Yuan, Jie; Chen, Xiaodong; Wang, Chuandong (Frontiers in Endocrinology, 2022)
Bone marrow mesenchymal stem cells (BMSCs) have been used in stem cell-based therapy for various diseases, due to their self-renewing and differentiation ability into various types of cells and immunoprivileged properties. However, the proliferation capability and functionality of BMSCs are known to decline with aging, which severely impairing the extensive applications of BMSCs-based therapies. To date, the exact mechanism involved in cellular senescence of BMSCs remains unclear. RNA is the initial molecular form of the origin of life. It is the transmitter and important regulator of genetic information expression. There are many kinds of small noncoding RNAs with different functions in cells, which regulate important life activity processes in multiple dimensions, including development process, gene expression, genomic stability and cellular senescence. In this study, replicative senescence model of hBMSCs was established and the expression changes of small noncoding RNAs during senescence was detected by small RNA high-throughput sequencing analysis and qPCR. Small RNA sequencing showed that there were significant differences in the expression of 203 miRNAs, 46 piRNAs, 63 snoRNAs, 12 snRNAs and 7 rasiRNAs. The results of qPCR which for the verification of the sequencing results showed that there were significant differences in the expression of 24 miRNAs, 34 piRNAs, 34 snoRNAs and 2 snRNAs. These findings might provide novel insight into hBMSCs senescence and contribute to the development of corresponding targeting anti-senescence strategies.